Blow Flies from Forest Fragments Embedded in Different Land Uses: Implications for Selecting Indicators in Forensic Entomology. Issue 1 (6th August 2015) - de Souza, Mirian S.; Pepinelli, Mateus; de Almeida, Eduardo C.; Ochoa‐Quintero, Jose M.; Roque, Fabio O.
Abstract: Given the general expectation that forest loss can alter biodiversity patterns, we hypothesize that blow fly species abundances differ in a gradient of native vegetation cover. This study was conducted in 17 fragments across different landscapes in central Brazil. Different land cover type proportions were used to represent landscape structure. In total, 2334 specimens of nine species of Calliphoridae were collected. We used principal component analysis (PCA) to reduce dimensionality and multicollinearity of the landscape data. The first component explained 70%, and it represented a gradient of forest‐pasture land uses. Alien species showed a wide distribution in different fragments with no clear relationship between the abundance values and the scores of PCA axes, whereas native species occurred only in areas with a predominance of forest cover. Our study revealed that certain native species may be sensitive to forest loss at the landscape scale, and they represent a bioindicator in forensic entomology.